2007
DOI: 10.1002/art.22706
|View full text |Cite
|
Sign up to set email alerts
|

The role of vascular cell adhesion molecule 1/ very late activation antigen 4 in endothelial progenitor cell recruitment to rheumatoid arthritis synovium

Abstract: Objective. Marrow-derived endothelial progenitor cells (EPCs) are important in the neovascularization that occurs in diverse conditions such as cardiovascular disorders, inflammatory diseases, and neoplasms. In rheumatoid arthritis (RA), synovial neovascularization propels disease by nourishing the inflamed and hyperproliferative synovium. This study was undertaken to investigate the hypothesis that EPCs selectively home to inflamed joint tissue and may perpetuate synovial neovascularization.Methods. In a coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 38 publications
5
67
0
2
Order By: Relevance
“…It is important to note, that this microvascular expansion is occurring before clinical symptoms appear. Synovial neovascularization creates a direct conduit for the entry into the joint of circulating leukocytes that exacerbate inflammation, and provides nutrients to the hyperproliferative synovium [45].…”
Section: Redox Regulation Of Endothelial Progenitor Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is important to note, that this microvascular expansion is occurring before clinical symptoms appear. Synovial neovascularization creates a direct conduit for the entry into the joint of circulating leukocytes that exacerbate inflammation, and provides nutrients to the hyperproliferative synovium [45].…”
Section: Redox Regulation Of Endothelial Progenitor Cellsmentioning
confidence: 99%
“…This might then lead to increased RA synovial blood vessel formation in pannus, perpetuating chronic inflammatory disease [47]. In collagen induced arthritis Silverman et al [45] observed EPC cells in the inflammatory infiltrate of arthritis joins, whereas they did not detect these cells in the joint lining form control animals. This correlates well with observations that the number of EPC in human RA synovial tissue samples was elevated 25-fold over the number of EPCs localized in normal synovial tissue [45].…”
Section: Redox Regulation Of Endothelial Progenitor Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several lines of evidence indicate that RA is associated with aberrant and severe vasculogenesis (i.e. the de novo formation of blood vessels) within the inflamed joints (Paleolog, 2009, Grisar et al, 2007, Grisar et al, 2005, Herbrig et al, 2006, Hirohata et al, 2004, Jodon de Villeroche et al, 2010, Ruger et al, 2004, Silverman et al, 2007. One of the first observations of vasculogenesis in RA was the discovery that the synovial fluids from patients with RA contained a low molecular weight vasculogenesis factor apparently identical to that derived from tumours (Brown et al, 1980).…”
Section: Rheumatoid Arthritismentioning
confidence: 99%